CO2-induced reversible morphology transition from giant worms to polymersomes assembled from a block-random segmented copolymer. Issue 15 (4th March 2015) - Wang, Wei; Liu, Hanbin; Mu, Meng; Yin, Hongyao; Feng, Yujun
Abstract : Reversible morphology transition between giant worms and polymersomes self-assembled from a block-random segmented copolymer is reported. Abstract : Well-defined block copolymers represent "stars" among amphiphilic compounds for self-assembly. However, few studies have been directed to their block-random "hybrid" counterparts. In this work, a segmented diblock copolymer containing one random block, PEO113 - b -P(4VP90 - r -DEAEMA30 ), was prepared via the RAFT technique from the hydrophilic poly(ethylene oxide) block and a random hydrophobic block copolymerized from 2-(diethylamino)ethyl methacrylate (DEAEMA) and 4-vinyl pyridine (4VP). It was found that first the copolymer in aqueous media could self-assemble into vesicles, which then fuse hierarchically into giant worm-like micelles similar to shish kebab, with length and diameter of ca. 15 μm and 215 nm, respectively. After bubbling CO2 into the copolymer solution up to saturation (pH 5.43), the giant worms transform into polymersomes with a diameter about 75 nm, which is considerably larger than that of the spherical micelles assembled from the same polymer treated with HCl (pH 3.32). The vesicles obtained could revert to worm-like aggregates after depleting CO2 by bubbling N2 . Protonation–deprotonation of the PDEAEMA unit, the intensive steric hindrance effect from the adjacent 4VP groups and hydrogen bonding between different 4VP units and free H2 O in the interior of polymersomes accounted for such a CO2 -driven reversible morphology transition.